Penerapan Teknologi Informasi dalam Reformasi Birokrasi pada Bidang Pendidikan - krisnandari, dian; Wiharta, Dewa Made; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi Elektro, 2019)
Universities are currently implementing information technology to create bureaucratic reform. This is done because the demands of the era and information technology are increasingly growing to be more sophisticated. In higher education both management and service are supported by the role of information technology. In the application of information technology, it certainly must be supported by apparatus resources that have good performance. In higher education the application of information technology is used in managing performance and service management. The application of information technology in performance management will encourage universities to achieve their mission. While in the service process, the application of information technology will have a positive impact because services will be carried out efficiently, effectively and transparently. Information technology is applied to services to create a service that is fast, precise, efficient and professional. In addition, to create good governance in bureaucratic reform, information technology must be integrated so as to foster rapid information between units in higher education. The application of information technology in higher education is one of the main steps in realizing bureaucratic reform. Keywords — Higher Education, Bureaucratic Reform, Information Technology.